Developing a catch-up model of technology: a grounded theory approach. Issue 4 (17th February 2021) - Saghafi, Fatemeh; Mohaghar, Ali; Kashiha, Monireh
Abstract : Purpose: Catch-up is a process during which the countries that are behind the technological borders try to reduce their technological gaps. For a company or country in the catch-up process, a suitable level of technological capabilities and absorption capacity is necessary as a fixed advance requirement. This paper aims to develop a catch-up model of technology. Design/methodology/approach: This study reviewed 90 published articles in the field of business management in Q1 and Q2 journals from the very beginning to the year of 2018 so that a framework can be presented for a catch-up. This framework has been obtained according to the process of grounded theory and by combining the previous studies. Findings: Accordingly, a framework of six categories has been presented including causal factors, main category, background factors, intervening factors, strategies and consequences. Finally, three general approaches including independence, collaboration and cooperation, are introduced and each of these categories has been described in a spectrum of this approach. Originality/value: This is the first study to conceptualize a catch-up model of technology by grounded theory.